2019
DOI: 10.1002/jsfa.10167
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative properties of Moringa oleifera kernel oil from different extraction methods during storage

Abstract: BACKGROUND: Moringa oleifera (MO) kernel oil is categorized as a high-oleic oil that resembles olive oil. However, unlike olive trees, MO trees are largely present in most subtropical and tropical countries. In these countries, therefore, the benefits of oleic acid can be obtained at a cheaper price through the consumption of MO kernel oil. This study reports on the effect of different extraction methods on oxidative properties of MO kernel oil during storage for 140 days at 13, 25, and 37 ∘ C. RESULTS: All aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Table 5 also highlights oleic acid as the dominant fatty acid in batches Y and Z. However, the values obtained were higher (79.22-79.65%) as compared to those reported by Mat Yusoff et al [4] in the case of crude MO kernel oil (~75%) and by Sánchez-Machado et al [9] in the case of refined MO kernel (71-72%) produced using different refining stages of neutralization, degumming, and bleaching. Similarly, the total content of oleic, palmitic, stearic, and linolenic acids comprised approximately 98% of the total fatty acids in both Batches Y and Z, while only~87% of these fatty acids were present in refined MO kernel oil as reported by Sánchez-Machado et al [9].…”
Section: Effect Of Dnb Refining On the Iodine Value And Fatty Acid Comentioning
confidence: 63%
See 3 more Smart Citations
“…Table 5 also highlights oleic acid as the dominant fatty acid in batches Y and Z. However, the values obtained were higher (79.22-79.65%) as compared to those reported by Mat Yusoff et al [4] in the case of crude MO kernel oil (~75%) and by Sánchez-Machado et al [9] in the case of refined MO kernel (71-72%) produced using different refining stages of neutralization, degumming, and bleaching. Similarly, the total content of oleic, palmitic, stearic, and linolenic acids comprised approximately 98% of the total fatty acids in both Batches Y and Z, while only~87% of these fatty acids were present in refined MO kernel oil as reported by Sánchez-Machado et al [9].…”
Section: Effect Of Dnb Refining On the Iodine Value And Fatty Acid Comentioning
confidence: 63%
“…This shows that the DNB refining process employed did not change the degree of unsaturation of the oil. In an earlier study conducted by Mat Yusoff et al [4], lower IVs of 54-65 g I 2 /100 g of oil were reported. These differences may be due to the different oil extraction methods employed.…”
Section: Effect Of Dnb Refining On the Iodine Value And Fatty Acid Comentioning
confidence: 85%
See 2 more Smart Citations
“…The sweet melon seed oil used during the current study also showed a positive/healthy impact on hypercholotrolemia. Moreover, cholesterol management through diet therapy could be the safest strategy as some other scientists have also recommended the safe use of Moringa olifera , 18 dairy products with specific strains of Lactobacillus, 19 watermelon, 20 and coumarins 21 to control hyperlipidemia.…”
Section: Resultsmentioning
confidence: 99%